2022
DOI: 10.52142/omujecm.39.4.15
|View full text |Cite
|
Sign up to set email alerts
|

The role of inflammatory markers in the diagnosis of extraperitoneal endometriosis

Abstract: Hospital between 2015 and 2021. Prior to the study, approval was obtained from the Clinical Research Ethics Committee of Gaziosmanpaşa University (project number: 21-KAEK-173/ 05.08.2021). The study was planned as a retrospective study in which 28 patients with extraperitoneal subcutaneous endometriosis were enrolled. Patient data were obtained from hospital records. As for the inclusion criteria, patients who were operated for extraperitoneal endometriosis and whose pathology was endometriosis externa were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 16 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…Besides, there was no significant relationship between the inflammatory marker levels in patients who underwent surgery because of endometriosis in different locations with various symptoms. 34 Contrary to the findings of the present study, based on a study that aimed to investigate the diagnostic value of combination markers of NLR and CA-125 for differentiating endometrioma from other benign ovarian cysts, the NLR and CA-125 levels were assessed separately and combined. Based on the findings of this research, neutrophils, lymphocytes, and NLR were higher in women with endometriosis than in women without it.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…Besides, there was no significant relationship between the inflammatory marker levels in patients who underwent surgery because of endometriosis in different locations with various symptoms. 34 Contrary to the findings of the present study, based on a study that aimed to investigate the diagnostic value of combination markers of NLR and CA-125 for differentiating endometrioma from other benign ovarian cysts, the NLR and CA-125 levels were assessed separately and combined. Based on the findings of this research, neutrophils, lymphocytes, and NLR were higher in women with endometriosis than in women without it.…”
Section: Discussionmentioning
confidence: 62%
“…In this research, no significant statistical difference was observed in the routine laboratory outcomes of the patients and inflammatory markers. Besides, there was no significant relationship between the inflammatory marker levels in patients who underwent surgery because of endometriosis in different locations with various symptoms 34 …”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations